-2(7p+1)=4(p-5)

Simple and best practice solution for -2(7p+1)=4(p-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(7p+1)=4(p-5) equation:



-2(7p+1)=4(p-5)
We move all terms to the left:
-2(7p+1)-(4(p-5))=0
We multiply parentheses
-14p-(4(p-5))-2=0
We calculate terms in parentheses: -(4(p-5)), so:
4(p-5)
We multiply parentheses
4p-20
Back to the equation:
-(4p-20)
We get rid of parentheses
-14p-4p+20-2=0
We add all the numbers together, and all the variables
-18p+18=0
We move all terms containing p to the left, all other terms to the right
-18p=-18
p=-18/-18
p=1

See similar equations:

| 3x-55=73 | | 7c+3–5c=15 | | 7-3=8-8(x+2)+2x | | 3/4x+8/1=41 | | 9+6(x+4)=8-5 | | 3x-9x+7=-9-(-4) | | 28=u+10(5) | | 0.8x=1.75 | | 9x-8x+7=-8 | | 3/4(x+9)=15  | | 8=−18+3/8(16−40n) | | -58=2(2+n)-3(-6n-6) | | -8(7n+7)=-224 | | 92=-4(2r—5) | | 2(7+7x)=-98 | | -26d=364 | | 3(x-1)=6(1/2+8) | | 10x-6x-x=15 | | 19-7n=7(-3n-3)-2 | | 1/2r+-3/2=2r+-12 | | 15=60-1.5x | | -10=x/4-8 | | 91=7(5+b) | | 4/5(x)=7/4 | | -6=9x-8x+3 | | 6.5=n+9 | | -75=3(6x+5) | | 3/5+3/2x-1=0 | | 74=2(3x+7) | | 48=4(9x+3) | | 6x+3-7=6x-4 | | 3x/2+1/2=2x/3-2/3 |

Equations solver categories